Evaluasi Kinerja Keuangan Dengan Menggunakan Profitabilitas Periode Sebelum dan Sesudah Akuisisi Pada Perusahaan Pengakuisisi : Studi Kasus Pada PT Plaza Indonesia Realty, TBK Tahun Periode 2011-2017 (International Forum of Researchers and Lecturers, 2024)
This research aims to evaluate the financial performance of the acquiring company using profitability indicators in the period before and after the acquistion process. The case study was conducted at PT Plaza Indonesia Realty, Tbk, during the period 2011-2017, involving in-depth analysis of the company's financial reports. The research method used includes collecting and analyzing financial data from the period before and after the acquisition. Profitability is evaluated by considering various financial ratios, including net profit, gross profit margin, and operating profit margin. This analysis aims to identify the significant impact of the acquisition process on the company's financial health. It is hoped that the research results will provide a better understanding of changes in a company's financial performance after undergoing an acquisition. These findings can provide a basis for company management in making strategic decisions, while also providing insight for stakeholders regarding the impact of acquisitions on company profitability. This research not only contributes to business and management practitioners, but also contributes to academic literature related to evaluating financial performance and corporate acquisition strategies. It is hoped that the conclusions of this research will provide valuable guidance in an ever-changing and competitive business context.